Hybrid ARQ schemes employing coded modulatioin and sequence combining - DENG, Robert H. (Institutional Knowledge at Singapore Management University, 1995)
In this paper, we propose and analyze two hybrid automatic-repeat-request (ARQ) schemes employing bandwidth efficient coded modulation and coded sequence combining. In the first scheme, a trellis-coded modulation (TCM) is used to control channel noise; while in the second scheme a concatenated coded modulation is employed. The concatenated coded modulation is formed by cascading a Reed-Solomon (RS) outer code and a block coded modulation (BCM) inner code. In both schemes, the coded modulation decoder, by performing sequence combining and soft-decision maximum likelihood decoding, makes full use of the information available in all received sequences corresponding to a given information message. It is shown, by means of analysis as well as computer simulations, that both schemes are capable of providing high throughput efficiencies over a wide range of signal-to-noise ratios. The schemes are suitable for large file transfers over satellite communication links where high throughput and high reliability are required